Exercise-induced changes in QT interval are smaller in COPD patients and have no impact on mortality. Issue 3 (16th March 2017) - Boutou, Afroditi K.; Franks, Russell; Mohan, Divya; Mantziari, Lilian; Wong, Tom; Hopkinson, Nicholas S.; Polkey, Michael I.
Chronic obstructive pulmonary disease (COPD) is a systemic disorder with significant pulmonary and extrapulmonary manifestations [1]. The right and left heart and the great vessels may be affected [2]. Specifically, patients with COPD (especially those with hypoxaemia) have functional alterations in cardiac autonomic modulation, manifested by tachycardia at rest, reduced baroreflex sensitivity, reduced heart rate variability and abnormal recovery of heart rate following exercise [3]. COPD patients establish a flat shortening of QT interval during maximum exercise, irrespectively of medication taken http://ow.ly/XMrb308wUZt